2019
DOI: 10.1111/tbed.13355
|View full text |Cite
|
Sign up to set email alerts
|

A viral metagenomic analysis reveals rich viral abundance and diversity in mosquitoes from pig farms

Abstract: Mosquitoes harbour a diversity of viruses and are responsible for several mosquito‐borne viral diseases of humans and animals, thereby leading to major public health concerns, and significant economic losses across the globe. Viral metagenomics offers a great opportunity for bulk analysis of viral genomes retrieved directly from environmental samples. In this study, we performed a viral metagenomic analysis of five pools of mosquitoes belonging to Aedes, Anopheles and Culex species, collected from different pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 92 publications
(97 reference statements)
0
14
0
Order By: Relevance
“…In particular, mosquitoes of the Aedes and Culex genera are well adapted to human environments, making them the most important transmission vectors for arthropod-borne viruses (arboviruses) such as Dengue virus, Zika virus, or West Nile virus [ 1 ]. Nevertheless, arboviruses sensu stricto are not the only viruses that replicate in mosquito vectors [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, mosquitoes of the Aedes and Culex genera are well adapted to human environments, making them the most important transmission vectors for arthropod-borne viruses (arboviruses) such as Dengue virus, Zika virus, or West Nile virus [ 1 ]. Nevertheless, arboviruses sensu stricto are not the only viruses that replicate in mosquito vectors [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have performed viral metagenomics on field mosquitoes collected from different countries (including the United States, Puerto Rico, China, Kenya, Australia, Sweden, etc. ), mainly focusing on novel virus discovery (16)(17)(18)(19)(20)(21)(22)(23)(24). Some newly discovered mosquito-specific viruses (MSVs) have been proposed as future biological control agents against arboviruses (25)(26)(27) or as novel vaccine platforms (27) or used in diagnostic assays in chimeric virus formation with structural protein genes from arboviruses (27).…”
mentioning
confidence: 99%
“…Therefore, their role in the transmission of ASFV under field conditions seems possible only in very specific conditions. Concerning mosquitoes, Hameed et al (2019) showed that mosquitoes of the genera Aedes, Anopheles and Culex could feed on pigs. In another study, ASFV DNA sequences were identified in mosquito samples collected from an Estonian farm where pigs were infected with ASFV (Herm, Tummeleht, Jürison, Vilem, & Viltrop, 2019).…”
Section: Discussionmentioning
confidence: 99%